Low-Dose Quercetin Dephosphorylates AKT and Suppresses Proteins Related to Migration in Human Metastatic Uveal Melanoma Cells - Petra Fodor; József Király; Zsuzsanna Szabó; Katalin Goda; Barbara Zsebik; Gábor Halmos (Life)
Background: Uveal melanoma (UM) is the most common intraocular cancer of the eye, with high metastatic potential in adults. In 50% of patients, UM spreads to other tissues, causing a fatal outcome. Flavonoids are bioactive phenolic compounds found in fruits and plants, thus commonly present in the natural diet. Quercetin is the most remarkable agent among flavonols proved to have an anticancer effect. Thus, we aimed to investigate the effect of quercetin on a metastatic UM cell line MM28. Methods: MM28 cells were treated with increasing concentrations of quercetin (0.1–10 µM). The changes of proliferation and migration markers were studied both in gene and protein expression level by qPCR, Western blotting, and Proteome Profiler Human XL Oncology Array. Results: Quercetin had only a slight anti-proliferative effect on MM28 cells. However, 1 µM of quercetin significantly elevated the mRNA expression of the Maspin gene and downregulated MMP2 gene expression. In addition, the protein expression levels of pAKT, NF-κB, and MMP8 were significantly decreased by the treatment. Conclusions: Our findings indicate that low-dose (1 µM) quercetin treatment is able to suppress the expression of certain migration markers, and therefore, it might be a useful adjuvant compound to reduce metastasis formation of UM.